Optimal Power Allocation Based on Success Probability of SIC Detection in MWRC PNC - Li, Hao; Chang, Xiao-Wen; Champagne, Benoit (Conference proceedings - Canadian Conference on Electrical and Computer Engineering, 2022)
In this paper, We propose a novel power allocation scheme for physical-layer network coding (PNC) in uplink multi-way relay channels (MWRC). The power allocation is formulated as a constrained optimization problem under the transmitting power constraint of user terminals, aiming at maximizing the success probability of the successive interference cancellation (SIC) detection at the relay. optimizing over such a metric maximizes the probability of correctly detecting all user signals, which is critical to the network code generation at the relay. Specifically, We first develop a generalized closed-form success probability of the SIC detection on signals with pulse-amplitude modulation (PAM) at the relay. A constraint optimization is formulated over this probability subject to the poWer constraints of user terminals. We implement an evolutionary particle swarm optimization (PSO) algorithm to solve the problem whose cost function is complicated and not necessarily concave. The numerical results show that the proposed power allocation method can improve the quality of network code extraction at the relay.